Entre a universidade e o mercado de trabalho: percepção do egresso de administração sobre o conceito de responsabilidade social - Castro, Samara Mírian Nobre de (Universidade Federal Rural do Semi-Árido, 2017)
Corporate Social Responsibility has emerged and perpetuated itself in organizations as a response to state intervention, as a means of guaranteeing the current economic system. In general terms, society and the market have been demanding from the business community a socially responsible attitude in order to minimize not only existing social inequalities but also the negative impact caused by the development of activities in some sectors of the economy. The CSR also enters the organizations through the hands of the Professional Administrator, formed by the Universities, which give him concepts and practices aimed at the knowledge of the management field. Therefore, the present study analyzes the perception of management graduates, from the Universidade Federal Rural do Semi-Àrido, about four conceptual perspectives of CSR. The objective of this study is to identify the occurrence of changes in the conception of responsibility that the administrator experienced in his training and that which is practiced in the company in which he works. This is a qualitative and descriptive research, which selected 15 graduates of the last two pedagogical projects of the mentioned teaching institution, who work in administrative activities in the public and service sectors, in micro, small, medium and large companies. Interviews were used as a data collection tool, applied to graduates. The research showed that there are no changes in the conception of social responsibility that the administrator experienced in his / her formation, however, this one is not able to be effective in the company that acts, because while the egress has its training focused on the Perspective of Competitive Advantage and Systemic, The organization, experiences practices focused on the Social Action Perspective
Keywords: Responsabilidade Social Corporativa; Perspectivas; Administrador Profissional; Corporate Social Responsibility; Perspectives; Professional Administrator; MULTIDISCIPLINAR::CIENCIAS AMBIENTAIS::AMBIENTE, TECNOLOGIA E SOCIEDADE